FORMAL DINIYAH EDUCATION CURRICULUM MANAGEMENT IN IMPROVING LEARNING SKILLS AT NURUL JADID BOARDING SCHOOL - Islamiyah, Wildatul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to find out: 1) To improve students' learning skills in the concentration of fiqh 2) To analyze and describe the planning, implementation and evaluation of learning 3) To understand curriculum management in formal diniyah education. This study uses a qualitative descriptive analysis with a case study approach. Research results show in the form of curriculum evaluation.